Development and psychometric testing of the gender misconceptions of men in nursing (GEMINI) scale among nursing students. Issue 4 (4th July 2022) - Montayre, Jed; Alananzeh, Ibrahim; Bail, Kasia; Barnewall, Kate; Beament, Tania; Campbell, Steve; Carmody, Cathy; Chan, Alex; Donnelly, Frank; Duff, Jed; Ferguson, Caleb; Gibson, Jo; et al.
Abstract : Background: Misconceptions about men in nursing may influence recruitment and retention, further perpetuating the gender diversity imbalance in the nursing workforce. Identifying misconceptions and implementing early intervention strategies to address these deep-rooted stereotypes remain challenging but is considered critical to support students who are commencing a nursing career. Objective: To develop and evaluate the psychometric properties of the 'Ge nder Mi sconceptions of meN in nursI ng (GEMINI) Scale. Design: Cross-sectional survey. Methods: Pre-registration nursing students enrolled in undergraduate nursing programmes across 16 nursing institutions in Australia were surveyed from July to September 2021. The 17-item self-report GEMINI Scale measured the gender misconceptions of men in nursing. Results: Of the 1410 completed surveys, data from 683 (45%) women were used for exploratory factor analysis showing a one factor structure, while data from 727 men (47%) were used for confirmatory factor analysis of the 17-item GEMINI Scale, which showed a good model fit. The scale demonstrated high internal consistency (Cronbach's alpha of 0.892). Men were found to have higher gender misconceptions ( p  < 0.001) while respondents who: (a) identified nursing as their first career choice ( p  = 0.002); (b) were in their final year of programme enrolment ( p  = 0.016); and (c) engaged in health-related paid work ( p  = 0.002) had lower gender misconceptions. Conclusion: The GEMINI Scale is a robust, valid, reliable, and easy to administer tool to assess misconceptions about men in nursing, which may potentially influence academic performance and retention. Identifying and addressing specific elements of misconceptions could inform targeted strategies to support retention and decrease attrition among these students. Impact statement: Genderism harms nursing, as well as the men and women working in the profession. Recruitment and retention of men into nursing is needed to cultivate male role models and diversify the workforce, however this is impeded by negative portrayals in popular culture and misconceptions entrenched in society.